Penguatan Keuangan Sosial Syariah Dalam Mengatasi Kemiskinan Dan Krisis Kemanusiaan Di Kota Bengkulu - Isnaeni, Hany Meridha; Vera, Vety; Harpepen, Andi (Pakis Journal Institute, 2024)
Sharia social finance has an important role in efforts to overcome poverty and humanitarian crises in various regions, including Bengkulu City. Based on 2022 data, the number of poor people in Bengkulu reaches around 740,612 people or 15.73% of the total population. Strengthening sharia social finance through instruments such as zakat, infaq, and alms can be an effective solution for community economic empowerment and poverty reduction. This study aims to examine the contribution of sharia social finance in community empowerment and poverty reduction in Bengkulu, using a community-based economic model and social cooperation. With a qualitative descriptive method, this study finds that sharia social financial institutions such as cooperatives and sharia microfinance institutions have great potential in improving the welfare of the poor through access to financing and support for small and medium enterprises (SMEs). In addition, the sharia-based empowerment model has been proven to be able to reduce social and economic inequality, as well as create more sustainable economic development in Bengkulu City.